Madam Satan - Axt, William 1888-1959 (Warner Home Video, 2010)
"A man is bewitched by the mysterious Madam Satan he meets at a lavish masquerade ball. Does this mean the end of his marriage to the demure spouse he left at home? Not likely, because the temptress is really his wife in disguise! Cecil B. DeMille directs this pre-Code musical extravaganza about a wife who teaches her errant husband a lesson in love. The risqué plot is a hoot, but what really makes this film is its can-you-believe-it production values: the ball, held on a giant dirigible, features a balletic salute to electricity, complete with human spark plugs—and a party-ending bolt of lightning that renders the airship flightless, sending the revelers leaping for their lives. Amazingly, the actors do their own stunts! Happy landings!" [warnerbros.com]
Bildformat 1.33:1 (4:3)
Original: USA 1930
Keywords: Film; DVD-Video